Synchronous and longitudinal effects of employee commitment on intellectual, social and affective engagement - Abu-Hamour, Husam Mahmmud Jamil (Business: Theory and Practice, 2018)
The aim of this research is to examine if there are any synchronous or longitudinal effects of employee commitment on employee engagement. The former is measured as a whole construct using affective, continuous and normative dimensions of commitment introduced by Allen and Mayer (1990), while the latter is assessed by intellectual, social and affective dimensions of employee engagement suggested by Soane et al. (2012). The rationale behind conducting this research is twofold. First, to fill the gap resulted from paucity of research conducted to examine the effects of employee commitment on employee engagement. Second, to overcome the most common limitation cited in many prior studies, namely the cross-sectional research design by performing a longitudinal research. The questionnaire used in this research is built by adopting items form prior literature. Then, it was administered over a two-time period to employees working in a large Jordanian hospitality setting located in Amman, the capital of Jordan. Two waves of data collection process have been achieved with a lag time of 12 months, that is, from August 2016 to August 2017. The number of returned questionnaires in the first measurement period is 487 (97.4%), while the number of returned questionnaires in the second measurement period is 473 (94.6%). The research hypotheses focus on the presence of synchronous or longitudinal effects of employee commitment, as well as intellectual, social, and affective dimensions of employee engagement. The results indicate that employee commitment significantly as well as simultaneously affects employees’ intellectual engagement, while significantly and longitudinally affects their social and affective engagement. These findings contribute to the organizational behavior literature by showing that employee commitment does not only enhance employees’ immediate absorption in methods that could be used to improve the work, but also it builds up strong relationships among them and with their organization’s values and environment. Additionally, it boosts their emotional attachment to job tasks over time. Therefore, it is recommended that academic researchers along with practitioners should look at changes in employee attitudes that might occur in the future.